(3fbO GdQLGds - (3GdJaQjTj, eUWai Hf GdMSjf GdMSjfj, J HYO (B1030(3gs
(3ChdgG (B:s
(3ChdgG(B: (3WQjb GdTjN CHj WGdH GdCfHGQj hZjQg hajg CMeO Hf YHOhf hPcQg(B.. (3HYfhGf CMeO Hf YHO GdhGMOs
(3BNQgG (B:s
(3BNQgG(B: (3hgPG GdESfGO ef GdTjNjf GdCLdjf GdTjN aNQ GdOjf hGdSjO eLO GdOjf Yf GdTjN GdEeGe GdYdGeI LeGd GdOjf GdMSf Hf jhSa Hf GdNWjQ GdLjdj(B. (3hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 232s
(3GdPQjYI, L (B24: 167s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs